2003
DOI: 10.1053/jhep.2003.50106
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of treatment outcome in patients with chronic hepatitis C: Significance of baseline parameters and viral dynamics during therapy

Abstract: In patients with chronic hepatitis C virus (HCV) infection scheduled for a 48-week treatment period, premature discontinuation of treatment was previously recommended if HCV-RNA levels remained detectable at week 24 of therapy. Considering the number of side effects and treatment costs, measurement of initial viral decline during therapy may identify virologic nonresponse earlier than 24 weeks. We retrospectively analyzed 260 European patients treated with standard or pegylated interferon alfa (IFN-␣) and riba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
135
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(156 citation statements)
references
References 30 publications
15
135
0
6
Order By: Relevance
“…The use of both the ratio of γ-GT/ALT and IL28B single nucleotide polymorphism factors enhances the predictability of antiviral combination therapy. In several studies using both uni- and multivariate analysis, a significant association with treatment outcome using the γ-GT level and the serum ALT for predicting an SVR has been shown [11,12,13]. In contrast to the reported studies, the present investigation focused on the role of the pretreatment γ-GT/ALT ratio.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The use of both the ratio of γ-GT/ALT and IL28B single nucleotide polymorphism factors enhances the predictability of antiviral combination therapy. In several studies using both uni- and multivariate analysis, a significant association with treatment outcome using the γ-GT level and the serum ALT for predicting an SVR has been shown [11,12,13]. In contrast to the reported studies, the present investigation focused on the role of the pretreatment γ-GT/ALT ratio.…”
Section: Discussionmentioning
confidence: 91%
“…Laboratory parameters such as the level of ALT and γ-GT are associated with treatment outcome after antiviral therapy irrespective of receiving either dual or triple therapy combinations [7,11,12,13,16]. None of these studies, however, reported a cutoff value for these two laboratory factors that define a successful treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors have been identiied, including age, liver ibrosis, HCV genotype, HCV RNA levels, race, amino acid substitutions in the core and NS5A regions, and interleukin 28B polymorphisms have been reported as predictors of response to IFN therapy [26][27][28][29][30][31]. This study investigated whether HBV coinfection afects response to DAA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis, hemofiltration and peritoneal dialysis given to chronic dialysis patients infected with HCV significantly lower HCV RNA levels in the blood [17]. The change in serum HCV RNA levels after starting therapy is an important predictor of treatment outcome [18,19,20]. Especially, a 2-log reduction in the HCV RNA viral load by week 4 is a prerequisite to achieving SVR with PEG-IFN/RBV combination therapy [21].…”
Section: Discussionmentioning
confidence: 99%